2002
DOI: 10.1002/etc.5620210302
|View full text |Cite
|
Sign up to set email alerts
|

The potential for estradiol and ethinylestradiol degradation in english rivers

Abstract: Water samples were collected in spring, summer, and winter from English rivers in urban/industrial (River Aire and River Calder, Yorkshire, UK) and rural environments (River Thames, Oxfordshire, UK) to study the biodegradation potential of the key steroid estrogen 17beta-estradiol (E2) and its synthetic derivate ethinylestradiol (EE2). Microorganisms in the river water samples were capable of transforming E2 to estrone (E1) with half-lives of 0.2 to 9 d when incubated at 20 degrees C. The E1 was then further d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
233
2
15

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 389 publications
(269 citation statements)
references
References 34 publications
19
233
2
15
Order By: Relevance
“…This apparent anomaly in the increase in E1concentration is explained by the biological conversion of E2 to E1 during the treatment process and in the sludge route. This abnormal behaviour has also been observed in previous studies (Nasu et al, 2001;Jurgens et al, 2002;Hashimoto et al, 2007;Ren et al, 2007). This also explains why E1 persist in both the effluent and sludge from the WWTPs.…”
Section: Removal Rates Of Treatment Processessupporting
confidence: 87%
“…This apparent anomaly in the increase in E1concentration is explained by the biological conversion of E2 to E1 during the treatment process and in the sludge route. This abnormal behaviour has also been observed in previous studies (Nasu et al, 2001;Jurgens et al, 2002;Hashimoto et al, 2007;Ren et al, 2007). This also explains why E1 persist in both the effluent and sludge from the WWTPs.…”
Section: Removal Rates Of Treatment Processessupporting
confidence: 87%
“…Williams et al gave biodegradation and sorption as the predominant attenuation mechanisms for estradiol. This conclusion was based on the observation of a shorter half-life for estradiol in the river than what laboratory photolysis studies had suggested (22), paired with the unlikeliness of volatilization. Therefore, the remaining possible mechanisms are sorption and biodegradation.…”
Section: Examples Of River Attenuationmentioning
confidence: 98%
“…It would be difficult to think of a more environmentally relevant parameter than reproduction when attempting 2084 All Supplemental Data may be found in the online version of this article. See Table S1 for the number of citations and rank of all the ''Top 100'' papers, which in this essay are references [3][4][5][6][7][9][10][11][12][13][14][15]19,20].…”
Section: Answering the Important Challengesmentioning
confidence: 99%
“…There are undoubtedly very many unanswered questions relating to the issue of estrogens in the environment. For example, very little is known about the importance of degradation (by whatever means) in controlling the concentrations of estrogenic chemicals in the aquatic environment [19]; hence, predicting environmental concentrations of the chemicals of concern is still difficult. Similarly, many, and perhaps most, estrogenic chemical have a range of effects on aquatic organisms.…”
Section: Remaining Uncertainties and Future Research Directionsmentioning
confidence: 99%